Gendered impact of COVID-19 containment measures on unpaid care work and mental health in Europe: a scoping review protocol - Kathleen Pöge; Hande Gencer; Regina Brunnett; Maria A Marchwacka; Petra Rattay; Tobias Staiger; Hürrem Tezcan-Güntekin (BMJ Open)
Introduction Women are more likely than men to provide unpaid care work. Previous research has shown that lack of support for various forms of unpaid care work and work-family conflicts have negative impacts on caregivers’ mental health, especially among female caregivers. COVID-19 containment measures may exacerbate existing gender inequalities both in terms of unpaid care work and adverse mental health outcomes. This scoping review protocol describes the systematic approach to review published literature from March 2020 onwards to identify empirical studies and grey literature on the mental health impact of COVID-19 containment measures on subgroups of unpaid caregivers at the intersection of gender and other categories of social difference (eg, ethnicity, age, class) in Europe.Methods and analysis This scoping review is informed and guided by Arksey and O’Malley’s methodological framework. We will search the databases Medline, PsycINFO, Scopus, CINAHL, Social Sciences Abstracts, Sociological Abstracts as well as Applied Social Sciences Index & Abstracts (ASSIA) and hand-search reference lists of selected articles to identify relevant peer-reviewed studies. We will conduct a grey literature search using Google Scholar and targeted hand-search on known international and European websites and include reports, working papers, policy briefs and book chapters that meet the inclusion criteria. Studies that report gender-segregated findings for mental health outcomes associated with unpaid care work in the context of COVID-19 containment measures in Europe will be included. Two reviewers will independently screen all abstracts and full texts for inclusion, and extract general information, study characteristics and relevant findings. Results will be synthesized narratively.Ethics and dissemination This study is a review of published literature; ethics approval is not warranted. The findings of this study will inform public health research and policy. The results will be disseminated through a peer-reviewed publication and conference presentations.